2022
DOI: 10.1002/pi.6483
|View full text |Cite
|
Sign up to set email alerts
|

Erucamide/thermoplastic polyurethane blend with low coefficient of friction, high elasticity and good mechanical properties for intelligent wearable devices

Abstract: In this study, erucamide as a non-toxic and tasteless lubricant was melt blended with thermoplastic polyurethane (TPU) to reduce the coefficient of friction (COF) of TPU and thus to improve the wearing comfort of intelligent wearable devices. The results show that when the content of erucamide reaches percolation, erucamide can migrate to the TPU surface, forming a layer of lubrication film, and thus significantly reduces the COF of TPU. In addition, erucamide with amide groups can form hydrogen bonds with car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…As polymer development has advanced, erucamide has garnered extensive attention due to its outstanding tribological properties [18][19][20]. Jia TY et al [21] used erucamide as a lubricant to melt blended with thermoplastic polyurethane (TPU) to reduce the friction coefficient of TPU, thereby improving the wearing comfort of intelligent wearable devices. Velázquez JDH et al [22] linked erucamide to the graphene sheet and found that erucamide chains tend to remain closer together through pi-pi stacking interactions arising from the double bonds located at C 13 -C 14 , and that this arrangement of erucamide chains was responsible for the lower friction coefficient of erucamide brushes, which was a macroscopic consequence of cooperative quantum mechanical interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As polymer development has advanced, erucamide has garnered extensive attention due to its outstanding tribological properties [18][19][20]. Jia TY et al [21] used erucamide as a lubricant to melt blended with thermoplastic polyurethane (TPU) to reduce the friction coefficient of TPU, thereby improving the wearing comfort of intelligent wearable devices. Velázquez JDH et al [22] linked erucamide to the graphene sheet and found that erucamide chains tend to remain closer together through pi-pi stacking interactions arising from the double bonds located at C 13 -C 14 , and that this arrangement of erucamide chains was responsible for the lower friction coefficient of erucamide brushes, which was a macroscopic consequence of cooperative quantum mechanical interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research aims to achieve a delicate balance of coefficient of friction and mechanical performance as polyurethanes continue to enable emerging technologies ranging from biomedical implants to wearable devices that both demand flexibility, excellent hysteresis behavior, and mechanical durability. 7 Although polydiene-based triblock copolymers and polyurethane thermoplastic elastomers continue to dominate the marketplace, novel compositions are necessary to address the challenging application environments while also providing avenues for depolymerization. Fluorinated polymers have received intense scrutiny recently as many fluorinated compounds are defined as "forever chemicals" and research efforts will continue to explore the safe utilization of fluorinated polymers in the absence of fluorinated surfactants.…”
mentioning
confidence: 99%